(untitled) (El Hilo de la Fabula, 2015)
The critical editing of Diario de viaje a Oriente (1850−1851), y otras crónicas del viaje oriental, by Lucio V. Mansilla, did not only involve the general description of the two recently found manuscripts, but also the thorough examination of the material, the analysis of the textual variations arisen in their comparison —which evidence the author´s intention to improve the first version—, their comparison with travel literature written later by Mansilla himself, their situation in the historical, cultural and biographical context, and the restoration of both nineteenth century texts for readers in the twenty first century. Moreover, both manuscripts are a highly valuable source of information for research focused on the Spanish spoken in Buenos Aires in mid nineteenth century.